ANALISIS NILAI RELIGIUS DALAM NOVEL KETIKA MAS GAGAH PERGI KARYA HELVY TIANA ROSA - Jepri Arizal (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2018)
This research aims to analyze the religious values contained in the novel When Mas Gallant Go work Helvy Tiana Rosa. The object of research is novel titled When Mas Dashing Go. The method used is descriptive qualitative method. Mechanical research using data analysis techniques to determine the religious values contained therein. The research data in this novel are quotations in the form of words and sentences in the novel When Mas Dashing Go. Techniques used in data collection documentary studies. The research instrument is the researchers themselves as the main instrument. The results of his research is the value of human piety towards God, man's obedience to our fellow human beings and human obedience to himself.